Exploring Pedagogical Content Knowledge of Teachers: a Paradigm For Measuring Teacher’s Effectiveness - Abiola Tawa Ahmed; Yusuf Olayinka Shogbesan (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
When considering the present and the future of education, it is hard to ignore the importance of teachers' subject-matter expertise. Educators' pedagogical content knowledge (PCK) is crucial to the development of effective teaching practises and the implementation of effective curricula. Since PCK permits the integration of content and pedagogy, it has the potential to have a profound and long-lasting effect on students' academic performance. For educators to do their jobs well, they need to have a firm grip of relevant information, concepts, principles, and methods. This understanding will serve as a guide for appropriate pedagogical thinking and decision making. The pedagogical content knowledge (PCK) that is part of both the art and science of teaching, however, can be difficult to understand and evaluate. Classroom observations, content representations (CoRes), pedagogical and professional experience registries (PaP-eRs), structured and semi-structured interviews, stimulated recall interviews, artefacts from teachers' tasks, concept mapping, reflective journals, tests, and lesson observations are just a few of the complex and specialised procedures required to measure PCK. Paper and pencil assessments have been hailed as a potentially useful instrument for determining PCK due to the fact that they are a trustworthy, objective, and valid procedure that may be utilised with a greater volume of samples. The easiest way to obtain PCK data for triangulation purposes from several sources is to use a combination of these approaches.